The Effect of the Carbon Content on the Ductile Behavior of Reinforcing Steel - Malim, Wa Ode Amala Rabia; Djamaluddin, Rudy; Irmawaty, Rita; Fakhruddin, . (Engineering, Technology & Applied Science Research, 2025)
This study investigates the influence of the raw materials on the ductility of four threaded reinforcing steel commonly used in Indonesia, with the aim of ensuring compliance with the applicable standard (SNI 2052:2024). The chemical composition and mechanical properties of the threaded reinforcing steel were analyzed using Optical Emission Spectroscopy (OES) and the Universal Testing Machine (UTM), respectively. The chemical test results showed that sample S1 likely originated from cleaner raw materials than samples S2, S3, and S4, as indicated by the former’s simpler alloy content. Samples S1, S2, and S3 met the standard criteria for the maximum carbon content according to SNI 2052:2024, while sample S4 exceeded the standard carbon content limit. Additionally, the Carbon equivalent (Ceq) values of samples S1, S2, and S3 confirmed the standard requirements, specifically regarding the strength and toughness aspects. However, sample S4 showed a Ceq value of 0.7, which exceeded the standard limit. The mechanical analysis demonstrated Yield Strength (YS) and Ultimate Tensile Strength (UTS) values ranging from 431.2 MPa to 505.4 MPa and 614 MPa to 673 MPa, respectively. The average UTS/YS ratio was above 1.25, which is the minimum limit. All reinforcing steels studied in this paper met the mechanical property requirements.